2011
DOI: 10.1371/journal.pone.0016130
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Anti-Tuberculosis Drug Resistance in Kampala-Uganda Are Low and Not Associated with HIV Infection

Abstract: BackgroundDrug resistance among tuberculosis patients in sub-Saharan Africa is increasing, possibly due to association with HIV infection. We studied drug resistance and HIV infection in a representative sample of 533 smear-positive tuberculosis patients diagnosed in Kampala, Uganda.Methods/Principal FindingsAmong 473 new patients, multidrug resistance was found in 5 (1.1%, 95% CI 0.3–2.5) and resistance to any drug in 57 (12.1%, 9.3–15.3). Among 60 previously treated patients this was 7 (11.7%, 4.8–22.6) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 8 publications
7
48
2
Order By: Relevance
“…5 In a recent study performed in Kampala, 1.1% of 473 new cases were MDR-TB. 11 The last published information on drug resistance for Kenya dates from 13,14 Despite the limited number of previously treated cases, the proportion of MDR-TB was higher among previously treated cases than among new cases, as expected. No extensively drug-resistant TB cases were detected at any of the sites.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…5 In a recent study performed in Kampala, 1.1% of 473 new cases were MDR-TB. 11 The last published information on drug resistance for Kenya dates from 13,14 Despite the limited number of previously treated cases, the proportion of MDR-TB was higher among previously treated cases than among new cases, as expected. No extensively drug-resistant TB cases were detected at any of the sites.…”
Section: Discussionsupporting
confidence: 52%
“…Although poorly documented in population-based studies, the association between HIV infection and DR-TB remains controversial in sub-Saharan Africa. 11,[15][16][17] An independent association was reported in the last national drug resistance survey in Swaziland, a Table 3 Multidrug and isoniazid resistance among new TB and HIV co-infected patients Homa Bay, Kenya (n = 221) FLD = first-line drugs; TB = tuberculosis; H = isoniazid; R = rifampicin; E = ethambutol; S = streptomycin; MDR-TB = multidrug-resistant TB. country with very high HIV and DR-TB prevalence.…”
Section: Discussionmentioning
confidence: 96%
“…However, estimates of primary resistance to isoniazid in HIV-infected individuals in all three trial settings were low, ranging from 3.8% in Soweto (6), 7.5% in Nairobi (34), and 4-9% in Uganda (35,36), and unlikely to affect our results. A recent national drug resistance survey in Uganda found that primary isoniazid resistance has remained low at 5% (37).…”
Section: Discussionmentioning
confidence: 69%
“…An estimated 18 to 20% of all TB cases reported to the National Tuberculosis and Leprosy Program (NTLP) come from this city, making Kampala the highest-TB-burdened district in Uganda (NTLP unpublished data). Anti-TB drug resistance and TB-HIV coinfection rates are similar to those for the entire country (16).…”
mentioning
confidence: 58%